Psychological aspects of recurrent chest pain. - Kisely, S R (1993)
Of 113 consecutive patients admitted recurrently with chest pain 28% exhibited psychiatric morbidity using the GHQ-28 (General Health Questionnaire). Eighty patients had ischaemic heart disease, 17 had non-specific pain and 13 were excluded because of other organic causes for their pain. Of the non-specific group, seven had been admitted previously with chest pain. In common with previous studies of first admissions with non-specific chest pain, recurrent admissions were younger and predominantly male. They also had a history of greater alcohol and cigarette use than patients with ischaemic heart disease. Greater psychiatric morbidity was not demonstrated in this small group of patients. In spite of the absence of an organic aetiology, patients with non-specific pain showed similar rates of re-admission to those with ischaemic heart disease before and after the study. Further research is indicated to identify aetiological and maintaining factors for continued non-specific pain.